2014
DOI: 10.1371/journal.pone.0114532
|View full text |Cite
|
Sign up to set email alerts
|

The Predicted ABC Transporter AbcEDCBA Is Required for Type IV Secretion System Expression and Lysosomal Evasion by Brucella ovis

Abstract: Brucella ovis is a major cause of reproductive failure in rams and it is one of the few well-described Brucella species that is not zoonotic. Previous work showed that a B. ovis mutant lacking a species-specific ABC transporter (ΔabcBA) was attenuated in mice and was unable to survive in macrophages. The aim of this study was to evaluate the role of this ABC transporter during intracellular survival of B. ovis. In HeLa cells, B. ovis WT was able to survive and replicate at later time point (48 hpi), whereas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…For instance, we have recently developed a B . ovis attenuated mutant vaccine candidate strain that lacks an ABC transporter [36], which influences the virB -encoded Type IV secretion system [146] thus interfering with intracellular trafficking [147]. This vaccine strain provided only moderate protection in the mouse model, yielding a protection index of approximately 1.0 [120], whereas it surprisingly provided a very strong protection against experimental challenge in rams, preventing shedding of the wild type strain in the semen and urine, accumulation of inflammatory cells in the semen, and gross or microscopic lesions induced by wild type B .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we have recently developed a B . ovis attenuated mutant vaccine candidate strain that lacks an ABC transporter [36], which influences the virB -encoded Type IV secretion system [146] thus interfering with intracellular trafficking [147]. This vaccine strain provided only moderate protection in the mouse model, yielding a protection index of approximately 1.0 [120], whereas it surprisingly provided a very strong protection against experimental challenge in rams, preventing shedding of the wild type strain in the semen and urine, accumulation of inflammatory cells in the semen, and gross or microscopic lesions induced by wild type B .…”
Section: Discussionmentioning
confidence: 99%
“…can adapt to the intracellular environment upon activation of expression of certain virulence factors (Kohler et al 2002). Different strains of a given Brucella species may exhibit different intracellular kinetics (Harmon et al 1988, Kohler et al 2002, Silva et al 2014. This may explain the differences in intracellular and in vivo survival and multiplication observed in this study, whereas in vitro growth on solid medium was remarkably similar among these isolates.…”
Section: Discussionmentioning
confidence: 74%
“…A previous study demonstrated that a B. ovis specific ABC transporter is required for B. ovis survival in vivo and evasion from phagosome/lysosome fusion (Silva et al 2011b, Macedo et al 2015. Additionally, B. ovis-specific ABC transporter is required for normal expression of the virB-encoded T4SS since in the absence of this ABC transporter there is a post-transcriptional impairement of expression of virB-encoded proteins (Silva et al 2014). Indeed, B. ovis mutant strains lacking a functional B. ovis-specific ABC transporter (Silva et al 2011b) or the virB-encoded T4SS (Sá et al 2012) have similar phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the substrate of this ABC transporter is not known, it is required for expression of B. ovis virulence proteins, including Omp31, Sod, and the virB-encoded type IV secretion system (23), which is required for B. ovis intracellular survival and in vivo persistence (17). Furthermore, a B. ovis ⌬abcBA strain is capable of triggering humoral and cellular immune responses like the wild-type strain in rams; importantly, however, the mutant strain is not excreted in semen and urine (24).…”
mentioning
confidence: 99%